1999
DOI: 10.1007/s005310050238
|View full text |Cite
|
Sign up to set email alerts
|

Alpine remagnetization and tectonic rotations in the French Pyrenees

Abstract: A palaeomagnetic study of the 100 to 90 m.y. old alkaline igneous rocks of the French Pyrenees has in part revealed large between-site scatter caused by highly variable declination. Magnetomineralogical evidence suggests that the original titano-magnetite has undergone variable low-temperature oxidation through martitization and maghemitization processes, suggesting that the rocks have been remagnetized. When viewed in the context of the Upper Cretaceous-Lower Tertiary inclination pattern based on Portuguese p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Adding to the tectonic complexity of the region, clockwise rotation of the western extremity of the Cappadocian collage has been suggested by palaeomagnetism (PIPER et al, 2002). STORETVEDT et al (1999), based on a palaeomagnetic study of alkaline igneous rocks of the French Pyrenees concluded that during the Alpine climax the Iberian Peninsula first rotated 40°counterclockwise and then 70°clockwise. The reason for this rotational instability is that the Peninsula is located within the tectonically strained Alpine region, being squeezed in between the oppositely rotating Eurasia and Africa megablocks.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the tectonic complexity of the region, clockwise rotation of the western extremity of the Cappadocian collage has been suggested by palaeomagnetism (PIPER et al, 2002). STORETVEDT et al (1999), based on a palaeomagnetic study of alkaline igneous rocks of the French Pyrenees concluded that during the Alpine climax the Iberian Peninsula first rotated 40°counterclockwise and then 70°clockwise. The reason for this rotational instability is that the Peninsula is located within the tectonically strained Alpine region, being squeezed in between the oppositely rotating Eurasia and Africa megablocks.…”
Section: Discussionmentioning
confidence: 99%
“…Filled symbols represent data from : Smulikowski 1929;Mahmood 1973;Kudlásková 1987;Dostal & Owen 1998;Włodyka 2010 (Harangi & Árva-Sós 1993). Mesozoic teschenites are rare elsewhere although occurences have been documented in Georgia (Lebedev et al 2009), the French Pyrenees (Azambre et al 1992;Storetvedt et al 1999) and Russia (Transbaikalia - Metelkin et al 2004;Stupak et al 2004) where volcanic activity associated with teschenite emplacement occured during the Late Cretaceous (from 86 to 110 Ma).…”
Section: Figmentioning
confidence: 99%
“…( (a) Delacotte et al (1985); Barchi et al (1997); Le Callonnec et al (1997); Galbrun (1997); Thibal et al (1999); Storetvedt et al (1999); Galbrun and Gardin (2004).…”
Section: Implications For the Tectonic Evolution Of The Pyrenean Orogenmentioning
confidence: 99%
“…1.a and c), and two sectors in the North: (1) Upper Cretaceous-Cenozoic boundary in the North-West (number 8 in Fig. 1.a) (Barchi et al, 1997;Delacotte et al, 1985;Galbrun, 1997;Galbrun and Gardin, 2004;Le Callonnec et al, 1997;Storetvedt et al, 1999;Thibal et al, 1999), ( 2 (Gisbert, 1981(Gisbert, , 1983 found in the west-central Pyrenees: the Paleozoic Basque Massifs on one hand, with variable recorded rotations, and the south Pyrenean Zone on the other hand, where there is a lack of large vertical axis rotations.…”
Section: Introductionmentioning
confidence: 99%